Light-Weight Solution to Defend Implantable Medical Devices against Man-In-The-Middle Attack - Belkhouja, Taha; Mohamed, Amr; Al-Ali, Abdulla K.; Xiaojiang Du; Guizani, Mohsen (2018 IEEE Global Communications Conference (GLOBECOM), 2018)
Nowadays, Implantable Medical Devices (IMDs) rely mainly on wireless technology for information exchange. In spite of the many advantages wireless technology offers to patients in terms of efficiency, speed and ease; it puts the patients' health in serious danger if no proper security mechanism is deployed. The IMDs rely generally on resources that are relatively simple and sometimes require surgery to be altered. Therefore, common security mechanisms cannot be simply implemented in fear of consuming all the resources held for healthcare purposes. A certain balance between security and efficiency must be found in each IMD architecture. In this work, we try to avoid encryption algorithms to protect IMDs from Man-In-The-Middle (MITM) attacks. Encryption is generally used to protect communication confidentiality. However, this method is still a subject for replay and MITM attacks. In this work, we propose to create a signature protocol that protects IMDs from MITM attempts using less resources than common encryption/decryption algorithms. This signature algorithm is dynamic, which means that the signature output depends on a key and the same message can have different signatures if this key is different. This dynamic part will be introduced using chaotic generators.